Genetic variation of safflower (Carthamus tinctorius L.) and related species revealed by ISSR analysis - Bagmohammadi, Hamed; Pahlevani, Mohammadhadi; Ahmadikhah, Asadollah; Razavi, Seyed Esmaeil (Plant Breeding and Seed Science, 2012)
Genetic diversity of eight genotypes of Carthamus tinctorius L., two populations of C. oxyacanthus, and one population of C. lanatus was investigated using inter-simple sequence repeat (ISSR) markers. All samples were uniquely distinguished by 10 ISSR primers with 144 bands which generated 100% polymorphism. Furthermore, the ISSR markers could separate three safflower species properly, that highlights the effectiveness of this marker system for phylogenetic studies. The most and least informative primers were ISSR9 (PIC=0.367) and ISSR2 (PIC=0.254), and some primers were more efficient in detecting polymorphism in one species than for the others. Unweighed pairgroup method with arithmetical averages (UPGMA) cluster analysis enabled construction of a dendrogram for estimating genetic distances among different populations. The result of cluster analysis suggested that cultivated and wild populations of C. oxyacanthus had close relationship with each other and far relationship with C. lanatus. The extreme genetic dissimilarity was observed between genotypes of C. tinctorius and C. lanatus populations. Based on the results, C. oxyacanthus could introduce favorable genes to cultivated safflower via inter-specific hybridization in breeding programs. Nei’s gene diversity index, Shannon’s index and percent of polymorphic loci showed that Isfahan ecotype of C. oxyacanthus had the highest variation at DNA level in relation to populations of other species. The ISSRs developed in this research along with those recently studied by other researchers will contribute to construct genetic map with a density sufficient for safflower molecular breeding.